Prickly postglacial pioneers: freshwater plankton community composition influences fatty acid desaturase (FADS2) copy number in Southern Greenland threespine sticklebacks ... - Hudson, Cameron; Twining, Cornelia; Moosmann, Marvin; Greenway, Ryan; Feulner, Philine; Matthews, Blake (Zenodo, 2024)
The adaptation of marine fish to freshwater environments includes prodigious examples of rapid evolution. Given the scarcity of ω-3 long-chain polyunsaturated fatty acids (LC-PUFA) in freshwater, we expect selection to be strong on fish transitioning to freshwater habitats and yet the underlying ecological causes of genomic and phenotypic differentiation are poorly understood for traits associated with lipid content and composition. Threespine stickleback (Gasterosteus aculeatus) have repeatedly colonized, and adapted to, freshwater habitats across the northern hemisphere. These freshwater populations often show elevated copy number of the fatty acid desaturase 2 gene (FADS2), which increases the biosynthetic capacity of LC-PUFA. The starkly lower content of LC-PUFA in freshwater compared to marine prey, especially docosahexaenoic acid (DHA), likely imposes strong positive selection on freshwater fish for either increased biosynthesis or greater dietary acquisition of LC-PUFA. The recently colonized and ... : Funding provided by: Swiss Polar InstituteROR ID: https://ror.org/02z9ca723Award Number: PAF-2020-005 Funding provided by: Swiss National Science FoundationROR ID: https://ror.org/00yjd3n13Award Number: 31003A_175614 ...